Evaluation of the effectiveness of antenatal corticoid in preterm twin and single pregnancies: a multicenter cohort study - Assad Gonçalves-Ferri, Walusa; Martinez, Francisco Eulógio; Martins-Celini, Fábia Pereira; de Almeida, João Henrique Carvalho Leme; Procianoy, Renato; Duarte, José Luiz Muniz Bandeira; Carvalho, Elaine Alvarenga Almeida; de Lima Mota Ferreira, Daniela Marques; Alves Filho, Navantino; Santos, Juliana Paula; Gimenez, Carolina Boschi; do Santos, Cristina Nunes; et al. (Taylor & Francis, 2021)
Background: The effects of antenatal corticosteroids (ANSs) on twins are not well established. Objective: To determine the impact of ANS use according to the number of fetuses. Methods: Retrospective cohort study of newborns between 23 and 33 weeks of gestational age, birth weight from 400 to 1499 g, without malformations, delivered at 20 public university hospitals from 2010 to 2014. Exposed group: Received ANS (any time, any dose) and no exposed group: no received ANS. Analysis of birth conditions and clinical outcomes. Association of variables, relative risks, and 95% confidence intervals estimated from the adjustment of log-binomial regression models. Results: About 7165 premature infants were analyzed: 5167 singleton, 937 twins, and 104 triplets. Characteristics of gestations with one, two, or three fetuses not receiving ANS were similar. Reduced hemodynamic instability in single and twins gestations in the first 72 h were observed (Adj R 2 Twins = 0.78; 95% CI = 0.69–0.86) (Adj R 2 Singles = 0.79; 95% CI = 0.62–0.99). Reduced peri-intraventricular hemorrhage (Adj R 2 Twins = 0.54; 95% CI = 0.36–0.78) (Adj R 2 singles = 0.54; 95% CI = 0.36–0.78); and early sepsis reduction on single and triplex gestations (Adj R 2 triplex = 0.51; 95% CI = 0.27–0.94) (Adj single R 2 = 0.51; 95% CI = 0.27–0.94) were observed. Conclusions: This study demonstrates ANS produces an important protective factor for severe intraventricular hemorrhage and hemodynamic instability in single and multiple pregnancies. ANS had a protective effect on death and birth conditions improvement just in single gestations. Regarding respiratory aspects was not observed the protective effect in the single or multiple gestations.
Keywords: antenatal corticoid; multiple births; neonatology; neurology; Twins